Strategi Efektif Manajemen Sumber Daya Manusia dalam Meningkatkan Kinerja Karyawan di Era Bisnis Modern - Khaeruman Khaeruman; Tabroni Tabroni (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research explores effective human resource management (HR) strategies with the aim of improving employee performance in the context of dynamic changes in the global business environment. This research uses qualitative methods and a case study approach. This research involves all employees in a particular organization as a population, with a sample selection of experienced employees in various aspects of HR management. Research instruments include in-depth interviews, direct observation, and document review. The research results show that rigorous recruitment and selection provides a solid foundation for long-term productivity, while continuous training and development increases employee adaptability to changing work environments. Effective communication creates a transparent and productive work environment, while constructive feedback plays an important role in improving employee performance and creating a work culture focused on development and higher achievement. The impact of HR management strategies on employee performance involves increased productivity, work-life balance, motivation, engagement, career development, and effective performance management. This research provides guidance and recommendations to organizations to face the dynamics of the current business environment and achieve long-term success by identifying key factors that influence employee performance and designing strategies accordingly.